ANALYSIS OF LEVEL OF BOTH SHOULDERS IN PHYSICAL THERAPY STUDENTS (International Journal of Physiotherapy, 2017)
Background: During lectures, usually students sit in an awkward position, for prolonged period of time and that may cause postural instability. For a good posture, bilateral landmarks should be on same level, when viewed from front or behind. Therefore, both shoulders should also be on same level as well. Any alteration in level of shoulders in healthy individual may lead to deformity in spine or extremity. The objective of this study was to analyze the level of both shoulders in the physical therapy students and to find its correlation with the perception of students about their shoulder balance.Methods: An observational (cross – sectional) study was conducted on students of Doctor in Physical Therapy (DPT) from colleges of Physical Therapy, Karachi. 100 Students were selected by Simple Random Sampling technique. Data from students was collected by administering a questionnaire. It includes close-ended questions. Afterwards, the level of both shoulders of the students, were assessed by using Scoliosis Meter.Results: Response from students showed that 79% of them assumed that both shoulders are in same level. When level of shoulder of students was assessed by scoliosis meter, it showed that 37% students have absolute level shoulder. Spearman’s Correlation coefficient (r = 0.046, p= 0.65) showed a weak, positive correlation between perception of the students about shoulder level and assessment of shoulder tilt.Conclusion: This showed that the perception of students about level of both shoulders was not correlated to the actual levels of the shoulders. Hence, as they were not assuming it uneven, so they may not pay any attention to keep themselves straight.